Exploring continuity equation via a modeling activity: in the context of crowd science. (2nd April 2020) - Yuksel, Tugba; Tekbıyık, Ahmet; Avsar Erumit, Banu
Abstract: Using problems from real life contexts which is related to learners' environment or their culture plays an important role in their learning that concept. In this regard, science educators especially physics educators search for real-life domain of theoretical concepts for effective science teaching and they consider analogical and physical models as an opportunity in their instruction. In the presented activity, we worked with 66 senior pre-service science teachers from our science teaching methods course. We used crowd movements as a real-life domain of our analogical models to scientifically explain a stampede case, then utilized physical model to explore continuity equation. Real life problem based scenarios could be used while taking advantage of the 3 D modeling in teaching of scientific principle. As a result, we found that pre-service teachers were able to make scientific explanation for causes of stampedes by using modeling activity. High school teachers and upper-level instructors could benefit from including the modeling activity introduced in this study to help their students understand the concepts related to continuity equation by designing a physical model based on an analogical model. Via the physical model, students are able to make predictions, observations, interpretations and explanations of a complex and abstract scientific phenomenon.